La divinización real en Mesopotamia: una teología política - Vidal, Jordi (ARYS. Antigüedad: Religiones y Sociedades, 2015)
The aim of this article is to analyze different examples of royal divinization attested in the history of Ancient Mesopotamia. The individual study of the examples demonstrates that the divinization of the king was an exceptional ideological tool, always used with a political purpose.